Manajemen Kepala Sekolah Dalam Pembinaan Profesionalisme Guru SMK Negeri 1 Pancur Batu - Imanuel Tarigan; Amini Amini; Faisal Rahman Dongoran (Departement of Mathematics Education, 2023)
This study aims to describe the management of school principals in fostering teacher professionalism at SMK Negeri 1 Pancur Batu. The research approach used was qualitative with a descriptive method, namely knowing and giving an overview of an objective fact and situation that occurred in the field, with research informants at SMK Negeri 1 Pancur Batu. The results of this study indicate that the management of the principal of SMK Negeri 1 Pancur Batu in fostering teacher professionalism is carried out well. This is indicated by 4 aspects, namely (1) in the planning aspect, the school principal has implemented efforts to improve the quality of education and teacher professionalism; (2) organizational aspects, the principal involves all school members to be involved in all forms of activity; (3) implementation aspect: in practice the school principal has a program implemented, namely providing opportunities for teachers to attend training, seminars, and activities related to teacher professional competence; and (4) evaluation aspect: evaluation really needs to be done to influence the level of achievement of the goals that have been set previously.